Identification of the causal relationship between sleep quality, insomnia, and oral ulcers - Qianxi Liu; Jiongke Wang; Tiannan Liu; Xin Zeng; Xuefeng Zhang (BMC, 2023)
Abstract Background Multiple epidemiological studies have posited a potential association between sleep quality and the risk of oral diseases, yet the resulting conclusions have remained contentious, and the presence of a causal link remains equivocal. In this study, we aimed to investigate the causal relationship between sleep duration, insomnia, and common oral diseases. Methods We utilized genetic correlation and two-sample Mendelian randomization analyses based on summary statistics from genome-wide association studies of sleep duration (N = 460,099), insomnia (N = 462,341), mouth ulcer (N = 385,026), oral cavity cancer (N = 4,151), and periodontal disease (N = 527,652). Results Our results revealed a negative genetic correlation between sleep duration and mouth ulcer (genetic correlation: -0.09, P = 0.007), while a positive genetic correlation between insomnia and mouth ulcer was observed (genetic correlation: 0.18, P = 2.51E-06). Furthermore, we demonstrated that longer sleep duration is significantly associated with a reduced risk of mouth ulcers (OR: 0.67, 95% CI: 0.54-0.83, P = 2.84E-04), whereas insomnia is nominally associated with an increased risk of mouth ulcers (OR: 1.40, 95% CI: 1.01-1.95, P = 0.044). In contrast, no significant association was detected between sleep quality and periodontal disease or oral cavity cancer. Conclusions This work provides robust evidence to support the notion that enhanced sleep quality may confer a decreased risk of oral ulcers, thereby bearing considerable clinical relevance.